Uncommon radiological findings: a case report - Tandjung, Yeti Rosalina Muslim; Chu, Pei Hong; Nambiar, Phrabhakaran; Ibrahim, Norliza (Wiley, 2007)
A 50-year-old friendly and attractive Chinese lady was examined by the Primary Care Unit, Faculty of Dentistry, University of Malaya. Her requests for treatment included implants and crowns. Two periapical radiographs of teeth 16 and 48 were taken to aid diagnosis. Interestingly, pin-lke radio-opaque objects were found over the crown of the impacted tooth 15 and also tooth 17. These objects were initially interpreted as silver points or radiographic artifacts but further investigation employing panoramic radiography revealed the distribution of more radio-opaque objects in the orofacial region. Based on a review of the literature and the opinion of experienced radiology and oral surgery lecturers, these foreign radio-opaque objects were diagnosed as susuks or charm needles.